2014
DOI: 10.1002/pssa.201400008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ag doping on the microstructure and photoluminescence of ZnO nanostructures

Abstract: ZnO nanostructures were obtained by metal-organic chemical vapour deposition via Ag catalyst assisted growth in a temperature range of 200 -500 °C. Growth at temperatures above 500 °C resulted in vertically aligned ZnO nanorods. Ag incorporation into ZnO up to 0.4 at. % promoted creation of basal plane stacking fault (BSF) defects and corrugation of the side facets of the nanorods. The presence of BSFs give rise to an additional photoluminescence peak with a wavelength of ~386 nm, which is slightly red-shifted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The Ag Zn energy formation is known to be smaller than the one for Ag I . Therefore, Ag uses to substitute Zn, moving the ZnO gap toward reduced energy levels and placing it as an excellent candidate for a p-type semiconductor [39]. In other words, the technique confirms the obtainment of ZnO and the partial substitution by Ag in its structure.…”
Section: Photoluminescencementioning
confidence: 72%
See 1 more Smart Citation
“…The Ag Zn energy formation is known to be smaller than the one for Ag I . Therefore, Ag uses to substitute Zn, moving the ZnO gap toward reduced energy levels and placing it as an excellent candidate for a p-type semiconductor [39]. In other words, the technique confirms the obtainment of ZnO and the partial substitution by Ag in its structure.…”
Section: Photoluminescencementioning
confidence: 72%
“…This is due to the low working temperature applied with the employed method, which results in the formation of extremely small crystallites (or particles) [38]. Here, when the particles are present in single crystals, the term crystallite can be used with the same meaning [39].…”
Section: Characterization Of Partial Replacement (Doping)mentioning
confidence: 99%
“…With highly coordinated sites, such as terrace sites being considered inactive in the OCM reaction, the increase of the lower coordinated sites explains the observed higher activity of the Mn-doped CaO. It is also quite reasonable that this effect is limited since highly isolated foreign ions can have a large impact on the surface structure by introducing lattice distortions, strain, stress (Khranovskyy et al, 2014), when the foreign atoms are getting close to each other, shown by the signal broadening in the EPR spectra (Figure 6B), the effect might be canceled out. Seeing a similar behavior with the Ni and Mn series also supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Interestingly, 1D ZnO nanostructures including nanorods (NRs), [ 12 ] nanowires (NWs), [ 13 ] nanorings, [ 14 ] and other morphologies [ 15 ] have advantages as fluorescence materials from properties such as a high aspect ratio, good chemical stability, wide bandgap, and high exciton binding energy. Researchers have improved the synthesis methods to obtain high‐quality ZnO nanostructures by altering surface morphology, [ 16 ] defect diffusion mechanism, and doping metal elements, [ 17 ] and then regulating the bandwidth and carrier concentration to obtain outstanding fluorescence properties. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[11] Interestingly, 1D ZnO nanostructures including nanorods (NRs), [12] nanowires (NWs), [13] nanorings, [14] and other morphologies [15] have advantages as fluorescence materials from properties such as a high aspect ratio, good chemical stability, wide bandgap, and high exciton binding energy. Researchers have improved the synthesis methods to obtain high-quality ZnO nanostructures by altering surface morphology, [16] defect diffusion mechanism, and doping metal elements, [17] and then regulating the bandwidth and carrier concentration to obtain outstanding fluorescence properties. [18] In addition, employing the strong coupling between local surface plasmon resonance and intrinsic exciton radiative recombination, some researchers propose an experimental heterojunction scheme to promote fluorescence properties by coating noble metal or other semiconductor material on the top of ZnO nanostructures.…”
Section: Introductionmentioning
confidence: 99%